The politics of Richard Wright : perspectives on resistance - Gordon, Jane Anna, 1976-; Zirakzadeh, Cyrus Ernesto, 1951- (Kentucky scholarship online., 2018)
A pillar of African American literature, Richard Wright is one of the most celebrated and controversial authors in American history. His work championed intellectual freedom amid social and political chaos. Despite the popular and critical success of books such as Uncle Tom's Children (1938), Black Boy (1945), and Native Son (1941), Wright faced staunch criticism and even censorship throughout his career for the graphic sexuality, intense violence, and communist themes in his work. Yet, many political theorists have ignored his radical ideas. In The Politics of Richard Wright, an interdisciplinary group of scholars embraces the controversies surrounding Wright as a public intellectual and author. Several contributors explore how the writer mixed fact and fiction to capture the empirical and emotional reality of living as a black person in a racist world. Others examine the role of gender in Wright's canonical and lesser-known writing and the implications of black male vulnerability. They also discuss the topics of black subjectivity, internationalism and diaspora, and the legacy of and responses to slavery in America. Wright's contributions to American political thought remain vital and relevant today. The Politics of Richard Wright is an indispensable resource for students of American literature, culture, and politics who strive to interpret this influential writer's life and legacy.